Potensi Precision Therapy Berbasis Shotgun Metagenomic Sequencing untuk Modulasi Mikrobiota Usus melalui Sinbiotik dan Pengaturan Pola Makan sebagai Strategi Baru dalam Manajemen Diabetes Mellitus Tipe 2 - Muhammad Rifqi Al Azim Rifqi (Jurnal Medika Hutama, 2025)
Abstrak Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder characterized by insulin resistance and impaired insulin secretion, commonly driven by sedentary lifestyles and unhealthy dietary habits. While conventional antidiabetic therapies are effective, they often cause adverse effects such as hypoglycemia and gastrointestinal disturbances. This review explores the potential of precision therapy via gut microbiota modulation as an innovative strategy in T2DM management. Shotgun metagenomic sequencing provides high-resolution insights into individual gut microbiome compositions, enabling tailored interventions. T2DM is frequently associated with gut dysbiosis, marked by reduced populations of Bifidobacteria and Akkermansia, which contributes to metabolic inflammation and insulin resistance. Synbiotics, a combination of prebiotics and probiotics, have shown efficacy in restoring microbial balance, enhancing short-chain fatty acid (SCFA) production, reinforcing intestinal barriers, and reducing systemic inflammation. Additionally, dietary regulation—particularly increased fiber intake and caloric restriction—supports microbiome diversity and glycemic control. A total of 156 articles were initially identified, and 7 studies meeting the inclusion criteria were selected and reviewed in detail. These studies collectively demonstrate the potential of synbiotic-based precision therapy supported by shotgun metagenomic profiling in improving metabolic outcomes among T2DM patients. This review advocates for the integration of microbiome profiling and personalized nutritional therapy as a promising avenue in T2DM treatment, with recommendations for future large-scale clinical validation. Keywords: Precision Therapy, Shotgun Metagenomic Sequencing, Gut Microbiota, Synbiotics, Type 2 Diabetes Mellitus, Dietary Intervention